REPEATED THERAPEUTIC LEUKAPHERESIS - A SOLE TREATMENT DURING PREGNANCY AS A BRIDGE BEFORE TYROSINE KINASE INHIBITORS FOR A PREGNANT WOMAN WITH CHRONIC MYELOGENOUS LEUKEMIA – A CASE REPORT AND DISCUSSION - Ivan Tonev; Chavdar Botev; Georgui Balatzenko; Milcho Mincheff (Journal of IMAB)
Objective: Chronic myelogenous leukemia (CML) is a disease, that in cases with high leukocyte numbers, is treated with hydration and cytoreductive therapy. Materials and Methods:A 20-year-old female patient, during a routine examination for pregnancy, presented with elevated white blood cells (WBC) count (over 275x109/L) and splenomegaly without any complaints. The diagnosis of Ph-positive CML was confirmed by cytology and PCR [presence of p210 type BCR::ABL1 [e13a2 (b2a2)] transcripts. Since she was in her 6th month of pregnancy, abortion or conventional treatment (tyrosine kinase inhibitors (TKI), chemotherapy and/or allogeneic haematopoietic stem cell transplant) were contraindicated due to the high risk for both the mother and the fetus. The patient was treated with two consecutive leukaphereses followed by weekly apheresis for about 3,5 months until the day of the delivery. Each procedure included the processing of 1000-1200 ml of whole blood with the separation of around 600 ml white blood cell concentrate and plasma. Results:The patient's WBC count was kept between 170 and 270 x 109/L until childbirth, and immediately after delivery, imatinib mesylate therapy was initiated.A healthy male child with a weight of 2250 kg and height of 46 сm was born. The mother achieved hematologic, cytogenetic and molecular remission within the next 6-9 months after initiation of tyrosine kinase inhibitor therapy. Discussion: The classical treatment for CML includes tyrosine kinase inhibitors, chemotherapy and/or allogeneic haematopoietic stem cell transplantation. All of these approaches have teratogenic potential, and therapeutic schemes should involve contraception. In cases with existing advanced pregnancy, therapeutic leukapheresis is a valid option for controlling WBC counts until the delivery date. Despite the later initiation of TKI therapy, the deep molecular response is still present thirteen years after the initiation of therapy.